Policy Entrepreneurship for Poverty Reduction - Maxwell, Simon; Court, Julius (PRACTICAL ACTION PUBLISHING, 2006)
Pages: 1-160 KerkoCite.ItemAlsoKnownAs: 10.3362/9781780445632 2339240:HTYCQ2TU 2405685:F6IAFHD3

DigEuLit: Concepts and Tools for Digital Literacy Development - Martin, Allan; Grudziecki, Jan (Innovation in Teaching and Learning in Information and Computer Sciences, 2006)
In the e-permeated society, a society also increasingly unpredictable and uncertain, “digital literacy” becomes not only a key factor in enabling participation in education, as well as employment and other aspects of social life, but also a means of gaining some understanding of the world. The DigEuLit project, funded by the EC eLearning Initiative, has a task of defining digital literacy and developing a framework and tools for digital literacy development in European educational settings. We have observed converging literacies which have gained new relevance in digital environments, and proposed a definition of digital literacy which focuses on the processes of using digital tools to support the achievement of goals in the individual’s life-situation. A suite of online tools is being developed to enable digital literacy progress to be tracked by teachers and learners, and evolution of these tools will continue beyond the life of the project.
Publisher: Routledge _eprint: https://doi.org/10.11120/ital.2006.05040249 KerkoCite.ItemAlsoKnownAs: 10.11120/ital.2006.05040249 2339240:MYSWTRD6 2405685:PUWANT8R

Closing the Digital Divide: Update From the Early Childhood Longitudinal Study - Judge, Sharon; Puckett, Kathleen; Bell, Sherry Mee (The Journal of Educational Research, 2006)
The authors examined the progress made toward equitable technology access and use over children's first 4 years of school. The sample consisted of 8,283 public school children who attended kindergarten, 1st, and 3rd grades. In 3rd grade, high-poverty schools had significantly more computers for instruction and a smaller ratio of children to computers than did low-poverty schools. Over the first 4 years of school, however, children attending low-poverty schools had significantly more access to home computers than did those attending high-poverty schools. Children's use of computers during 3rd grade differed by school-poverty status. Results indicate that access to, and use of, a home computer, the presence of a computer area in classrooms, frequent use of the Internet, proficiency in computer use, and low-poverty school status were correlated positively with academic achievement. In contrast, frequent use of software for reading was correlated negatively with reading achievement.
Publisher: Routledge _eprint: https://doi.org/10.3200/JOER.100.1.52-60 KerkoCite.ItemAlsoKnownAs: 10.3200/JOER.100.1.52-60 2339240:V6BL23DF 2405685:N35LVTCM
Keywords: Early Childhood Longitudinal Study; computer access in high- and low-poverty schools; first- and third-grade children; kindergarten

The logical chain: continuing professional development in effective schools - Ofsted (2006)
KerkoCite.ItemAlsoKnownAs: 2339240:6RVN2CE5 2405685:7W8DVFNS

National Information and Communication Technology (ICT) Strategy for Education and Training - Ministry of Education (Government of Kenya, 2006)
This Strategy undertaking was prepared by the Ministry of Education (MoE) in collaboration with stakeholders from the public, private, civil society and development partner sectors. It outlines how Information and Communication Technologies (ICTs) will be adopted and utilized to improve access, quality and equity in the delivery of education services in Kenya. The Strategy is based on the vision that: “ICTs is a universal tool in education and training”. The mission statement that inspires it is: “to integrate ICTs in education and training to improve access, learning and administration.” The overall objective of the plan is to ensure that systematic efforts are made towards strengthening adoption and use of ICT in the education sector with appropriate attention given to education development priorities as outlined in the Economic Recovery Strategy for Wealth and Employment Creation (ERSWEC, 2003-2007); Sessional Paper No. 1 of 2005 entitled “A Policy Framework For Education”, Training and Research and the United Nations’ Millennium Development Goals (MDGs). The challenges that are outlined in these policy documents include; the need to achieve Education For All (EFA) by 2015 in tandem with the national and international commitment, Universal Primary Education (UPE) by 2010, and to increase transition rate from primary to secondary schools from 47% to 70%. Policy documents in the education sector have given considerable attention to priorities related to access, quality, equity and relevance at all levels. This strategic plan considers and proposes that ICT can contribute substantially towards realization of these objectives. In addition, ICT has considerable potential to support implementation of Free Primary Education (FPE) and to address emerging challenges such as; overcrowded classrooms, high Pupil Teacher Ratios (PTRs) particularly in densely populated and semi-arid areas, shortage of teachers on certain subjects or areas, and relatively high cost of learning and teaching materials
Accepted: 2020-07-07T08:13:03Z KerkoCite.ItemAlsoKnownAs: 2339240:6L4NL6GN 2405685:J4JBMDND

Young children's use of video as a source of socially relevant information - Troseth, G. L.; Saylor, M. M.; Archer, A. H. (Child Development, 2006)
Although prior research clearly shows that toddlers have difficulty learning from video, the basis for their difficulty is unknown. In the 2 current experiments, the effect of social feedback on 2-year-olds' use of information from video was assessed. Children who were told "face to face" where to find a hidden toy typically found it, but children who were given the same information by a person on video did not. Children who engaged in a 5-min contingent interaction with a person (including social cues and personal references) through closed-circuit video before the hiding task used information provided to find the toy. These findings have important implications for educational television and use of video stimuli in laboratory-based research with young children.
Place: Hoboken Publisher: Wiley WOS:000237394700018 KerkoCite.ItemAlsoKnownAs: 10.1111/j.1467-8624.2006.00903.x 2339240:RLTHFNDK 2405685:53A22D6L
Keywords: behavior; blues-clues; comprehension; find; guide; imitation; infants; learn; perception; television

The Dimensional Change Card Sort (DCCS): a method of assessing executive function in children - Zelazo, Philip David (Nature Protocols, 2006)
The dimensional change card sort (DCCS) is an easily administered and widely used measure of executive function that is suitable for use with participants across a wide range of ages. In the standard version, children are required to sort a series of bivalent test cards, first according to one dimension (e.g., color), and then according to the other (e.g., shape). Most 3-year-olds perseverate during the post-switch phase, exhibiting a pattern of inflexibility similar to that seen in patients with prefrontal cortical damage. By 5 years of age, most children switch when instructed to do so. Performance on the DCCS provides an index of the development of executive function, and it is impaired in children with disorders such as attention-deficit/hyperactivity disorder (ADHD) and autism. We describe the protocol for the standard version (duration = 5 min) and the more challenging border version (duration = 5 min), which may be used with children as old as 7 years. *Note: In the version of the article originally published, the boat in the upper right of the figure was blue. It should be red. The error has been corrected in the HTML and PDF versions of the article.
shortDOI: 10/b9853h KerkoCite.ItemAlsoKnownAs: 10.1038/nprot.2006.46 10/b9853h 2339240:4NWH2QGZ 2405685:JDIERCD8

Think Scenarios, Rethink Education - OECD (OECD, 2006)
KerkoCite.ItemAlsoKnownAs: 10.1787/9789264023642-en 2405685:QD6BD9GQ

Paradigm Peace and the Implications for Quality - Bryman, Alan (International Journal of Social Research Methodology, 2006)
In this article it is shown that the paradigm wars that raged concerning the incompatibility of quantitative and qualitative research have largely subsided. In the process, discussions of epistemological and ontological issues have become less prominent. The peace that has broken out has proved to be more favourable to research combining quantitative and qualitative research than was the case during the paradigm wars. Drawing on interviews with social researchers who employ a mixed‐methods approach and on the literature, it is shown that a spirit of pragmatism with regard to combining quantitative and qualitative research prevails which encourages researchers to consider using mixed‐methods research when the research question is suited to it. However, the issue of which quality criteria should be employed in investigations combining quantitative and qualitative research has not been given a great deal of consideration. The author argues for a contingency approach, in which issues to do with quality are decided in relation to the nature of the study.
shortDOI: 10/b8wtt2 KerkoCite.ItemAlsoKnownAs: 10.1080/13645570600595280 10/b8wtt2 2339240:T3KNAFUP 2405685:RKS7ELJH

Optimising worked example instruction: Different ways to increase germane cognitive load - Paas, Fred; van Gog, Tamara (Learning and Instruction, 2006)
Worked examples are an effective instructional means to teach complex problem-solving skills. It has been argued that worked examples decrease extraneous load, enabling more Working Memory (WM) resources to be directed to activities that facilitate learning and transfer performance. Hence, cognitive load research has started to shift its focus towards finding instructional techniques that impose a germane cognitive load by stimulating the allocation of WM resources to such activities. This special issue provides an overview of recent experimental research on ways to further optimise the design and delivery of worked examples in order to foster learning and transfer.
shortDOI: 10/bg2wtc KerkoCite.ItemAlsoKnownAs: 10.1016/j.learninstruc.2006.02.004 10/bg2wtc 2405685:GQ7VHTE3

National Information and Communication Technology Policy - Zambia - Ministry of Communications and Transport (Government of Zambia, 2006)
KerkoCite.ItemAlsoKnownAs: 2339240:FMRERPT7 2405685:8VTMICTF

Demonstrating rigor using thematic analysis: A hybrid approach of inductive and deductive coding and theme development - Fereday, Jennifer; Muir-Cochrane, Eimear (International Journal of Qualitative Methods, 2006)
In this article, the authors describe how they used a hybrid process of inductive and deductive thematic analysis to interpret raw data in a doctoral study on the role of performance feedback in the self-assessment of nursing practice. The methodological approach integrated data-driven codes with theory-driven ones based on the tenets of social phenomenology. The authors present a detailed exemplar of the staged process of data coding and identification of themes. This process demonstrates how analysis of the raw data from interview transcripts and organizational documents progressed toward the identification of overarching themes that captured the phenomenon of performance feedback as described by participants in the study.
Publisher: SAGE Publications Inc KerkoCite.ItemAlsoKnownAs: 10.1177/160940690600500107 2405685:QC55NYB3 2486141:29R84E8T

Working memory in children with reading disabilities - Gathercole, Susan Elizabeth; Alloway, Tracy Packiam; Willis, Catherine; Adams, Anne-Marie (Journal of Experimental Child Psychology, 2006)
This study investigated associations between working memory (measured by complex memory tasks) and both reading and mathematics abilities, as well as the possible mediating factors of fluid intelligence, verbal abilities, short-term memory (STM), and phonological awareness, in a sample of 46 6- to 11-year-olds with reading disabilities. As a whole, the sample was characterized by deficits in complex memory and visuospatial STM and by low IQ scores; language, phonological STM, and phonological awareness abilities fell in the low average range. Severity of reading difficulties within the sample was significantly associated with complex memory, language, and phonological awareness abilities, whereas poor mathematics abilities were linked with complex memory, phonological STM, and phonological awareness scores. These findings suggest that working memory skills indexed by complex memory tasks represent an important constraint on the acquisition of skill and knowledge in reading and mathematics. Possible mechanisms for the contribution of working memory to learning, and the implications for educational practice, are considered.
shortDOI: 10/b59c23 KerkoCite.ItemAlsoKnownAs: 10.1016/j.jecp.2005.08.003 10/b59c23 2339240:HV2K4TBE 2405685:5A7J3C4R
Keywords: IQ; Mathematics; NOTdocs.opendeved.net; Reading disabilities; Short-term memory; Working memory

Scopus database: A review - Burnham, Judy F. (National Library of Medicine, 2006)
The Scopus database provides access to STM journal articles and the references included in those articles, allowing the searcher to search both forward and backward in time. The database can be used for collection development as well as for research. This review provides information on the key points of the database and compares it to Web of Science. Neither database is inclusive, but complements each other. If a library can only afford one, choice must be based in institutional needs.
KerkoCite.ItemAlsoKnownAs: 10.1186/1742-5581-3-1 2339240:6RMWD3XC 2405685:U9CFT7QG

Does changing behavioral intentions engender behavior change? A meta-analysis of the experimental evidence - Webb, Thomas L.; Sheeran, Paschal (Psychological Bulletin, 2006)
Numerous theories in social and health psychology assume that intentions cause behaviors. However, most tests of the intention- behavior relation involve correlational studies that preclude causal inferences. In order to determine whether changes in behavioral intention engender behavior change, participants should be assigned randomly to a treatment that significantly increases the strength of respective intentions relative to a control condition, and differences in subsequent behavior should be compared. The present research obtained 47 experimental tests of intention-behavior relations that satisfied these criteria. Meta-analysis showed that a medium-to-large change in intention (d = 0.66) leads to a small-to-medium change in behavior (d = 0.36). The review also identified several conceptual factors, methodological features, and intervention characteristics that moderate intention-behavior consistency.
shortDOI: 10/c9ffrz KerkoCite.ItemAlsoKnownAs: 10.1037/0033-2909.132.2.249 10/c9ffrz 2405685:FQQMQ9MQ
Keywords: Attitude; Cooperative Behavior; Female; Humans; Intention; Male; Social Behavior

Improving teaching quality in Guinea with interactive radio instruction - Burns, Mary (2006)
Guinea's Sous le Fromager project is an excellent example of radio as an effective delivery system for enhancing teachers’ basic content skills and for helping teachers with little or no instructional skills acquire those skills.
KerkoCite.ItemAlsoKnownAs: 2339240:IB9MSTJD 2405685:EB5MX5GI

The Effectiveness of Volunteer Tutoring Programs: A Systematic Review - Ritter, Gary; Denny, George; Albin, Ginger; Barnett, Joshua; Blankenship, Virginia (2006)
KerkoCite.ItemAlsoKnownAs: 2339240:WFIBLC8T 2405685:BSZTHPDM

Using thematic analysis in psychology - Braun, Virginia; Clarke, Victoria (Qualitative Research in Psychology, 2006)
Thematic analysis is a poorly demarcated, rarely acknowledged, yet widely used qualitative analytic method within psychology. In this paper, we argue that it offers an accessible and theoretically flexible approach to analysing qualitative data. We outline what thematic analysis is, locating it in relation to other qualitative analytic methods that search for themes or patterns, and in relation to different epistemological and ontological positions. We then provide clear guidelines to those wanting to start thematic analysis, or conduct it in a more deliberate and rigorous way, and consider potential pitfalls in conducting thematic analysis. Finally, we outline the disadvantages and advantages of thematic analysis. We conclude by advocating thematic analysis as a useful and flexible method for qualitative research in and beyond psychology.
KerkoCite.ItemAlsoKnownAs: 10.1191/1478088706qp063oa 2339240:ZG2T2YCR 2405685:K6VHKKI9
Keywords: epistemology; flexibility; patterns; qualitative psychology; thematic analysis

"A new beginning" Children, primary schools and social change in post-conflict Preah Vihear Province Cambodia - Geeves, Richard; Eng, Kim Ly; Lorn, Sa; Borrmei, Lon; Saran, Sok (Save the Children, 2006)
KerkoCite.ItemAlsoKnownAs: 2405685:QKDQ5FLL

Zanzibar Education Policy (Ministry of Education and Vocational Training, 2006)
KerkoCite.ItemAlsoKnownAs: 2339240:74HUJH9W 2405685:P9RU84Z5

Optimising learning and education in Africa: The language factor - Alidou, H.; Boly, A.; Brock-Utne, B.; Diallo, Y.S.; Heugh, K.; Wolff, H.E. (ADEA, UIE, GTZ, 2006)
KerkoCite.ItemAlsoKnownAs: 2339240:DZMRMG7P 2405685:SDDDDUBW

Teaching (with) disability: Pedagogies of lived experience - Anderson, Robert C. (Review of Education, Pedagogy, and Cultural Studies, 2006)
KerkoCite.ItemAlsoKnownAs: 10.1080/10714410600873258 2339240:9KZQH9K4 2405685:PMBFA6AQ

Teacher Education at a Distance: Impact on Development in the Community - Binns, Felicity; Wrightson, Tony (DFID, 2006)
KerkoCite.ItemAlsoKnownAs: 2405685:3IPM5K7Y
Keywords: C:Low- and middle-income countries; ⛔ No DOI found

Using thematic analysis in psychology - Braun, Virginia; Clarke, Victoria (Qualitative Research in Psychology, 2006)
Thematic analysis is a poorly demarcated, rarely acknowledged, yet widely used qualitative analytic method within psychology. In this paper, we argue that it offers an accessible and theoretically flexible approach to analysing qualitative data. We outline what thematic analysis is, locating it in relation to other qualitative analytic methods that search for themes or patterns, and in relation to different epistemological and ontological positions. We then provide clear guidelines to those wanting to start thematic analysis, or conduct it in a more deliberate and rigorous way, and consider potential pitfalls in conducting thematic analysis. Finally, we outline the disadvantages and advantages of thematic analysis. We conclude by advocating thematic analysis as a useful and flexible method for qualitative research in and beyond psychology.
Publisher: Routledge _eprint: https://www.tandfonline.com/doi/pdf/10.1191/1478088706qp063oa KerkoCite.ItemAlsoKnownAs: 10.1191/1478088706qp063oa 2339240:2V45ZJ8L 2405685:3ZMH9W8Q

The BSCS 5E Instructional Model: Origins and Effectiveness - Bybee, R; Taylor, J. A; Gardner, A; Van Scotter, P (BSCS (Biological Sciences Curriculum Study), 2006)
KerkoCite.ItemAlsoKnownAs: 2339240:NJ3BK7VN 2405685:JX7VKY7V

Education Management Information Systems (EMIS) in Latin America and the Caribbean: lessons and challenges - Cassidy, T (Inter-American Development Bank, 2006)
KerkoCite.ItemAlsoKnownAs: 2339240:8BQ9STIT 2339240:T6Y5INQI 2339240:UJBGNXBA 2405685:4AA66EFV 2405685:4LG5ZKEP 2405685:FE5G8PH4 4656463:G2RQ9X5X
Keywords: ⛔ No DOI found

Application of a Systems Approach to Distance Education - Daniel, Teresa A. (Proceedings of the 50th Annual Meeting of the ISSS-2006, Sonoma, CA, USA, 2006)
KerkoCite.ItemAlsoKnownAs: 2339240:VERZ4VBV 2339240:ZEQWKAD9 2339240:ZRRNGZP7 2405685:C9JUSLSE
Keywords: ⛔ No DOI found

Meeting EFA: Reaching the underserved through complementary models of effective schooling - DeStefano, Joseph; Hartwell, A.; Schuh-Moore, A.; Balwanz, D. (Academy for Educational Development (AED), 2006)
KerkoCite.ItemAlsoKnownAs: 2339240:VNT7QNLH 2405685:KLXN3KCY
Keywords: ⛔ No DOI found

Malawi National ICT for Development (ICT4D) Policy - Government of Malawi (2006)
KerkoCite.ItemAlsoKnownAs: 2339240:GDT8RMBE 2405685:PT3CV2YM
Keywords: ⛔ No DOI found

Using mixed-methods sequential explanatory design: From theory to practice - Ivankova, Nataliya V.; Creswell, John W.; Stick, Sheldon L. (Field Methods, 2006)
This article discusses some procedural issues related to the mixed-methods sequential explanatory design, which implies collecting and analyzing quantitative and then qualitative data in two consecutive phases within one study. Such issues include deciding on the priority or weight given to the quantitative and qualitative data collection and analysis in the study, the sequence of the data collection and analysis, and the stage/stages in the research process at which the quantitative and qualitative data are connected and the results are integrated. The article provides a methodological overview of priority, implementation, and mixing in the sequential explanatory design and offers some practical guidance in addressing those issues. It also outlines the steps for graphically representing the procedures in a mixed-methods study. A mixed-methods sequential explanatory study of doctoral students’ persistence in a distance-learning program in educational leadership is used to illustrate the methodological discussion.
KerkoCite.ItemAlsoKnownAs: 10.1177/1525822X05282260 2339240:VQGJ38ZH 2405685:86T8XIYL

Teacher motivation and incentives in Malawi - Kadzamira, Esme Chipo (Centre for Educational Research and Training, University of Malawi, 2006)
KerkoCite.ItemAlsoKnownAs: 2129771:5JBMK24W 2129771:5TI4XUFN 2339240:3RTX2ISG 2405685:RYZ5A4F2 4556019:IX6M7P8I 4556019:M4TPZI27 4752638:4I5N2859 4752638:7C6UCMHK
Keywords: C:Malawi; _C:Malawi MWI; ⛔ No DOI found

Teacher motivation and incentives in Malawi - Kadzamira, Esme Chipo (Centre for Educational Research and Training, University of Malawi, 2006)
KerkoCite.ItemAlsoKnownAs: 2129771:5JBMK24W 2129771:5TI4XUFN 2339240:3RTX2ISG 2405685:RYZ5A4F2 4556019:IX6M7P8I 4556019:M4TPZI27 4752638:4I5N2859 4752638:7C6UCMHK
Keywords: C:Malawi; _C:Malawi MWI; ⛔ No DOI found

Teacher motivation and incentives in Malawi - Kadzamira, Esme Chipo (2006)
KerkoCite.ItemAlsoKnownAs: 2339240:SWGNG2DL 2405685:VPVQV7I7

Teacher motivation and incentives in Malawi - Kadzamira, Esme Chipo (Centre for Educational Research and Training, University of Malawi, 2006)
KerkoCite.ItemAlsoKnownAs: 2129771:5JBMK24W 2129771:5TI4XUFN 2339240:3RTX2ISG 2405685:RYZ5A4F2 4556019:IX6M7P8I 4556019:M4TPZI27 4752638:4I5N2859 4752638:7C6UCMHK
Keywords: C:Malawi; _C:Malawi MWI; ⛔ No DOI found

DEEP IMPACT: an investigation of the use of information and communication technologies for teacher education in the global south - Leach, Jenny (DFID, 2006)
KerkoCite.ItemAlsoKnownAs: 2405685:RQHCLU3T
Keywords: ___working_potential_duplicate

DEEP IMPACT: an investigation of the use of information and communication technologies for teacher education in the Global South - Leach, Jenny; Ahmed, Atef; Makalima, Shumi; Power, Tom (DFID, 2006)
KerkoCite.ItemAlsoKnownAs: 2405685:RQHCLU3T 2405685:V427KR5D 2534378:7SP4UDPQ
Keywords: ___working_potential_duplicate; auto_merged

Quality of education and teacher learning: a review of the literature - Leu, Elizabeth; Price-Rom, Alison (American Institutes for Research under the EQUIP1 LWA; U.S. Agency for International Development, 2006)
KerkoCite.ItemAlsoKnownAs: 2339240:B7A7AZI7 2405685:7Z8J5D5F

Quality of Education and Teacher Learning: A Review of the Literature - Leu, Elizabeth; Price-Rom, Alison (American Institutes for Research under the EQUIP1 LWA Academy for Educational Development, 2006)
KerkoCite.ItemAlsoKnownAs: 2339240:K3KECM73 2405685:TTR5IKQQ

Quality of education and teacher learning: a review of the literature - Leu, Elizabeth; Price-Rom, Alison (American Institutes for Research under the EQUIP1 LWA; U.S. Agency for International Development, 2006)
KerkoCite.ItemAlsoKnownAs: 2339240:B7A7AZI7 2405685:7Z8J5D5F

English Language Teaching in Mauritius: A Need for clarity of vision regarding English Language Policy - Mahadeo, Satish Kumar (The International Journal of Language, Society and Culture, 2006)
KerkoCite.ItemAlsoKnownAs: 2405685:7ALSDVWF 4042040:YJ6L3RJF
Keywords: ⛔ No DOI found

Field-Based Models of Primary Teacher Training: Case Studies of Student Support Systems from Sub-Saharan Africa - Mattson, Elizabeth (Department for International Development, 2006)
KerkoCite.ItemAlsoKnownAs: 2405685:48KESELW
Keywords: C:sub-Saharan Africa; ⛔ No DOI found

National Information and Communication Technology Strategy for Education and Training - Ministry of Education, Kenya (2006)
KerkoCite.ItemAlsoKnownAs: 2405685:ZTFFZSKR

The Athens of West Africa: A History of International Education at Fourah Bay College, Freetown, Sierra Leone - Paracka, Daniel J. (2006)
This book is about Fourah Bay College (FBC) and its role as an institution of higher learning in both its African and international context. The study traces the College's development through periods of missionary education (1816-1876), colonial education (1876-1938), and development education (1938-2001).
KerkoCite.ItemAlsoKnownAs: 2339240:993UCWCL 2405685:3CTGQYRP

Systematic reviews in the social sciences: A practical guide - Petticrew, Mark; Roberts, Helen (Blackwell Publishing, 2006)
This book is a guide to planning and conducting a particular type of literature review, one that is increasingly used as a scientific tool: the systematic literature review. The book is aimed at social science researchers, but it provides a more general discussion of systematic reviews for those who want to use and understand them, but don't necessarily want to do one themselves. Most of the recent interest in systematic reviews focuses on reviews of the effectiveness of interventions, reflected in the growth of initiatives like the Campbell and Cochrane Collaborations. This book therefore focuses on reviews of effectiveness, but not exclusively. Systematic reviews are also widely used to synthesize other sorts of evidence, for example in order to answer questions about etiology (causes of problems), or about people's experiences, and we discuss and present examples of such reviews. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
KerkoCite.ItemAlsoKnownAs: 2339240:WXDFWS9M 2405685:KTBSA4AP
Keywords: Literature Review; Social Sciences

Rethinking Education Management Information Systems: Lessons from and Options for Less Developed Countries - Powell, Marcus (2006)
Donors and planners often have unrealistic expectations about what can be achieved in a short time period and underestimate the challenges facing EMIS.
KerkoCite.ItemAlsoKnownAs: 2339240:RQI7KJCY 2405685:TVYWHVG3 4656463:IKM46ZNW

Rethinking Education Management Information Systems: lessons from and options for less developed countries - Powell, Marcus (InfoDev, 2006)
KerkoCite.ItemAlsoKnownAs: 2339240:D7B95ZM6 2405685:T67DWXBM

Rethinking Education Management Information Systems: Lessons from and Options for Less Developed Countries - Powell, Marcus (2006)
Donors and planners often have unrealistic expectations about what can be achieved in a short time period and underestimate the challenges facing EMIS.
KerkoCite.ItemAlsoKnownAs: 2339240:RQI7KJCY 2405685:TVYWHVG3 4656463:IKM46ZNW

Tools for knowledge and learning: a guide for development and humanitarian organizations - Ramalingam, Ben (Overseas Development Institute, 2006)
OCLC: 749000861 KerkoCite.ItemAlsoKnownAs: 2339240:KAPZXX6J 2405685:4V6LJZNM

Aspirations, poverty, and economic change - Ray, Debraj (Understanding Poverty, 2006)
This essay discusses a particular aspect of poverty: its close and brutal association with a failure of aspirations. This is not an assertion about individuals who are poor; it is a statement about the condition of poverty itself. Poverty stifles dreams, or at least the process of attaining dreams. Thus, poverty and the failure of aspirations may be reciprocally linked in a self-sustaining trap. This essay seeks to draw out various aspects of this theme and, in the process, to introduce and discuss an aspirations-based view of individual behavior.
KerkoCite.ItemAlsoKnownAs: 10.1093/0195305191.003.0028 2339240:2T4ZNREX 2405685:BNLHW8HH
Keywords: aspirations failure; aspirations window; collective action; individual behavior; poor; social polarization

Universal Design for Learning: Is It for Everyone? - Rose, D; Meyer, A (2006)
Universal Design for Learning (UDL) stands at the forefront of contemporary efforts to create universal access to educational curricula for all students, including those with disabilities. The "universal" in UDL does not mean there is a single optimal solution for everyone. Instead, it underscores the need for flexible approaches to teaching and learning that meet the needs of different kinds of learners. In this first UDL Reader, Anne Meyer and David H. Rose, cofounders of CAST, the educational nonprofit that developed the UDL framework, bring together a collection of articles on the practical, classroom dimensions of the UDL revolution in education. The authors offer insights on learner differences, the capacities of new media in the classroom, and effective teaching and assessment practices. The volume also includes lessons from teacher professional development workshops, classroom-based research, and UDL practitioners themselves. A highly readable volume aimed particularly at school teachers and administrators, this book is also an uncommonly accessible introduction to UDL for all readers committed to creating improved and universal access to educational materials for all students. Following a preface (Anne Meyer and David H. Rose), this book contains the following chapters: (1) Applying Universal Design for Learning in the Classroom (Peggy Coyne, Patricia Ganley, Tracey Hall, Grace Meo, Elizabeth Murray, and David Gordon); (2) A UDL Case Story and Model Lesson: Reading Challenges in Geography and Social Studies (The Staff at CAST); (3) Frequent Questions about Universal Design for Learning (Grace Meo); (4) A Level Playing Field: UDL in the Classroom (Lani Harac); (5) Teacher Perspectives: UDL in the Elementary Classroom (Kirsten Lee Howard); (6) Teacher Perspectives: Strategy Instruction Goes Digital (Nicole Strangman); (7) Implications of Universal Design for Learning for Classroom Assessment (David H. Rose and Robert P. Dolan); (8) The Promise of New Learning Environments for Students with Disabilities (Bart Pisha and Skip Stahl); (9) Transforming the Textbook to Improve Learning (Skip Stahl); (10) Engaging the Text: Brain Research and the Universal Design of Reading Strategy Supports (David H. Rose and Bridget Dalton); and (11) Teaching Internet Literacy Strategies: The Hero Inquiry Project (Maya B. Eagleton, Kathleen Guinee, and Karen Langlais). An index is also included.
KerkoCite.ItemAlsoKnownAs: 2339240:RTHAM8C5 2405685:2IJJICCL

The Effect of Family Literacy Interventions on Children's Acquisition of Reading: From Kindergarten to Grade 3 - Senechal, Monique (American Psychological Association, 2006)
Goal. Educators believe that parents can help their children learn to read. But what evidence supports this belief? And if parent involvement does matter, what kinds of parent involvement are most efficient? The goal of this report was to review the scientific literature on parent involvement in the acquisition of reading from kindergarten to grade 3. Method. In the present review, parent involvement in literacy acquisition was narrowly defined to include parent-child activities that focus on reading. Moreover, the 14 studies that were analyzed were those that included an intervention where researchers tested whether parent involvement enhanced children’s literacy. Standard meta-analytic procedures were used to analyze the study outcomes.
8 citations (Crossref) [2024-02-28] KerkoCite.ItemAlsoKnownAs: 10.1037/e573272006-001 2339240:XBYMK5PU 2405685:Q6868QLC
Keywords: ⛔ No INSPIRE recid found

Beyond Instructional Design: Making Learning Design a Reality - Sims, Rod (Journal of Learning Design, 2006)
When we reflect on the emergence of online education and e-learning as the leading contender to confront the traditions of face-to-face teaching and learning, it is not only a case of better understanding the characteristics of online environments, but also timely to assess the relevance of theories and frameworks informing the design and implementation of those environments. Over the past twenty five years, the value of technology to education has been a significant focus of teachers, learners and institutional administration; it is also a period that has been characterised by lighthouse success stories, rigorous research, technological determinism and unfulfilled promises. As each new generation of technology appeared in the classroom (microcomputers, colour monitors, hypermedia, multimedia, internet), a new generation of early adopters appeared, each seemingly unaware of the research and knowledge gained by the previous generation. In this paper the argument is proposed that even with the strong foundation of knowledge that informs the appropriate ways to use technology for teaching and learning, too often that knowledge has been misunderstood or misused or ignored. The paper is based on the keynote presentation to the Online Learning and Teaching Conference held in Brisbane on September 23rd, 2005. The theme of the conference, "Beyond Delivery," was extremely timely as it marked the assertion that it was time to put the simple digitisation of materials behind us and focus on the active, engaging learning opportunities that effectively put the learning back into e-learning to take advantage of collaborative tools, learning communities and mediated conversation for new millennial learners. More importantly the statement that we are "beyond delivery" also suggests that it is time to embrace change and reflect on new ways to conceptualise the design of online learning environments. Through this paper an argument is presented for a proactive approach to the conceptualisation, formation and maintenance of online environments that cater specifically for the individual learner. Through an analysis of design strategies, proactive modelling and interactive metrics, a new framework is presented to address the pedagogy of online environments and present an alternative to common instructional design practices. For those committed to online teaching and learning environments populated with collaborating and reflective participants, this framework goes well beyond delivery to a pedagogy centred on emancipation and empowerment for the engaged learner.
Publisher: Queensland University of Technology KerkoCite.ItemAlsoKnownAs: 2405685:RX8KWKNW
Keywords: Active Learning; Audio Equipment; Cognitive Style; Communities of Practice; Computer Mediated Communication; Conferences (Gatherings); Cooperative Learning; Educational Technology; Electronic Learning; Empowerment; Epistemology; Feedback (Response); Guidelines; Instructional Design; Models; Online Courses; Student Role; Teacher Role; Teaching Methods; Video Technology; ⛔ No DOI found

A guide to developing the ICT curriculum for early childhood education. - Siraj-Blatchford, I; Siraj-Blatchford, J (Stylus Publishing, LLC., 2006)
KerkoCite.ItemAlsoKnownAs: 2339240:ZC6SPGTJ 2405685:2UIM9IDR

Learning from evidence in a complex world - Sterman, John D. (American journal of public health, 2006)
Publisher: American Public Health Association KerkoCite.ItemAlsoKnownAs: 10.2105/AJPH.2005.066043 2339240:S4A7BF3D 2405685:47LVMS7V

Law on Gender Equality - The National Assembly, Socialist Republic of Vietnam (2006)
KerkoCite.ItemAlsoKnownAs: 2339240:RBBKCTXS 2405685:HJ2YF688

Increasing student motivation: strategies for middle and high school teachers - Theobald, Margaret A. (Corwin Press, 2006)
This unique resource provides a wealth of theories and strategies for teachers to help spark students' motivations to learn and succeed beyond their formal schooling years.
Google-Books-ID: hYlyAwAAQBAJ KerkoCite.ItemAlsoKnownAs: 2339240:36JVNFDI 2405685:MU3JMLD8
Keywords: Education / General

Equivalency Programmes (EPs) for Promoting Lifelong Learning - UNESCO (2006)
KerkoCite.ItemAlsoKnownAs: 2339240:N5KURGZ8 2405685:S256T4H5

Convention on the Rights of Persons with Disabilities - United Nations (United Nations Human Rights Office of the High Commissioner, 2006)
Convention Ratifications/Accessions: 182 Signatories*: 164 Optional Protocol Ratifications/Accessions: 96 Signatories*: 94 (* Signatories include countries or regional integration organizations that have signed the Convention and its Optional Protocol) 10th Anniversary of the adoption of CRPD: 2006 to 2016 Infographic on the CRPD and the COSP (prepared October 2016: (Word, PDF) Status of Ratifications to the CRPD (prepared May 2016) (JPG, […]
KerkoCite.ItemAlsoKnownAs: 2339240:5IDS3FHB 2339240:9N929PHG 2339240:PQDH9LW2 2405685:3FCY2QN4 2405685:C5PEP2G4 2405685:ZCMN87NZ
Keywords: ⛔ No INSPIRE recid found

Learning styles and formative assessment strategy: enhancing student achievement in Web-based learning - Wang, K. H.; Wang, T. H.; Wang, W. L.; Huang, S. C. (Journal of Computer Assisted Learning, 2006)
The purpose of this research was to investigate the effects of formative assessment and learning style on student achievement in a Web-based learning environment. A quasi-experimental research design was used. Participants were 455 seventh grade students from 12 classes of six junior high schools. A Web-based course, named BioCAL, combining three different formative assessment strategies was developed. The formative assessment strategies included Formative Assessment Module of the Web-Based Assessment and Test Analysis system (FAM-WATA) (with six Web-based formative assessment strategies), Normal Module of Web-Based Assessment and Test Analysis system (N-WATA) (only with partial Web-based formative assessment strategy) and Paper and Pencil Test (PPT) (without Web-based formative assessment strategy). Subjects were tested using Kolb's Learning Style Inventory, and assigned randomly by class into three groups. Each group took Web-based courses using one of the formative assessment strategies. Pre- and post-achievement testing was carried out. A one-way ANCOVA analysis showed that both learning style and formative assessment strategy are significant factors affecting student achievement in a Web-based learning environment. However, there is no interaction between these two factors. A post hoc comparison showed that performances of the FAM-WATA group are higher than the N-WATA and PPT groups. Learners with a ‘Diverger’ learning style performed best followed by, ‘Assimilator’, ‘Accommodator’, and ‘Converger’, respectively. Finally, FAM-WATA group students are satisfied with six strategies of the FAM-WATA.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1365-2729.2006.00166.x shortDOI: 10/fgkwjr KerkoCite.ItemAlsoKnownAs: 10.1111/j.1365-2729.2006.00166.x 10/fgkwjr 2405685:HQSUKKNZ
Keywords: Kolb's learning style; WATA system; Web-based formative assessment; biology; e-learning effects; middle school

The Social Life of Technology: An Ecological Analysis of Technology Diffusion in Schools - Zhao, Yong; Lei, Jing; Frank, Kenneth A. (Pedagogies: An International Journal, 2006)
shortDOI: 10/d7h88f KerkoCite.ItemAlsoKnownAs: 10.1207/s15544818ped0102_5 10/d7h88f 2339240:5VZLQSJV 2339240:WS4YPJXX 2405685:CXPZTPRP 2405685:RZ7JQCIS